2017
DOI: 10.1373/clinchem.2016.257279
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lipid Biomarker Panel for the Detection of Heart Failure with Reduced Ejection Fraction

Abstract: OBJECTIVES:In this study we aimed to identify novel metabolomic biomarkers suitable for improved diagnosis of heart failure with reduced ejection fraction (HFrEF). METHODS:We prospectively recruited 887 individuals consisting of HFrEF patients with either ischemic (ICMP, n ϭ 257) or nonischemic cardiomyopathy (NICMP, n ϭ 269), healthy controls (n ϭ 327), and patients with pulmonary diseases (n ϭ 34). A singlecenter identification (n ϭ 238) was followed by a multicenter confirmation study (n ϭ 649). Plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The interpretation of NT pro-BNP in HD patients thus remains a complex issue not only due to its renal elimination but also due to a described increase in states of fluid overload [29]. Yet, it has previously been shown to be associated with higher mortality in HD patients [30] and has recently been successfully been implemented in the diagnostic process of HFrEF together with a lipid panel analysis and might therefore remain a practical tool for HF diagnosis in HD patients [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of NT pro-BNP in HD patients thus remains a complex issue not only due to its renal elimination but also due to a described increase in states of fluid overload [29]. Yet, it has previously been shown to be associated with higher mortality in HD patients [30] and has recently been successfully been implemented in the diagnostic process of HFrEF together with a lipid panel analysis and might therefore remain a practical tool for HF diagnosis in HD patients [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent study enrolling patients with either ischaemic or non-ischaemic cardiomyopathy, healthy controls and patients with pulmonary diseases, three specific metabolomic features belonging to the lipid classes of SMs, triglycerides and phosphatidylcholines together with N-terminal pro-B-type natriuretic peptide (NT-proBNP) distinguished patients with HF from healthy controls. 51 In addition, the diagnostic accuracy of this combination was significantly superior compared with the diagnostic accuracy of NT-proBNP alone. 51…”
Section: Cardiomyopathiesmentioning
confidence: 94%
“…In HF, both myocardial and systemic changes in glucose oxidation, catabolism, b-oxidation, and the urea cycle are responsible for observed alterations in metabolite levels [177]. Several studies have shown that a collection of metabolites can serve as diagnostic tools for HF [178][179][180][181]. However, changes in metabolite profiles seem not to be disease specific, because similar differences were observed in serum samples of patients with diseases such as nonHodgkin lymphoma, congestive HF, and communityacquired pneumonia (CAP) [182].…”
Section: Metabolitesmentioning
confidence: 99%